A modular mini-pad photon detector prototype for RICH application at the Electron Ion Collider. (April 2020) - Agarwala, J.; Azevedo, C.D.R.; Chatterjee, C.; Cicuttin, A.; Ciliberti, P.; Crespo, M.L.; Dalla Torre, S.; Dasgupta, S.; Gregori, M.; Levorato, S.; Menon, G.; Tessarotto, F.; et al.
Abstract: Experiments at the future Electron Ion Collider require excellent hadron identification in a broad momentum range, in harsh conditions. A RICH capable to fulfill the PID requirements of the EIC could use MPGD-based photon detectors with solid photocathodes for covering large surfaces at affordable cost, providing good effciency, high resolution and compatibility with magnetic field. Photon detectors realized by coupling THGEMs and Micromegas have been successfully operated at the RICH-1 detector of the COMPASS Experiment at CERN since 2016. A similar technology could be envisaged for an EIC RICH, provided a large improvement in the photon position resolution is achieved. An R&D effort in this direction is ongoing at INFN Trieste. Few prototypes with smaller pixel size (down to 3 mm x 3 mm) have been built and tested in the laboratory with X-Ray and UV LED light sources. A modular mini-pad detector prototype has also been tested at the CERN SPS H4 beamline. New data acquisition and analysis software called Raven DAQ and Raven Decoder have been developed and used with the APV-25 based Scalable Readout System (SRS), for the modular mini-pad prototype tests. The main characteristics of the new mini-pad hybrid MPGD-based detector of single photons are described and preliminary results of laboratory and beam tests are presented.